Youth Tobacco Access and Possession Policy Interventions: Effects on Observed and Perceived Tobacco Use - Jason, Leonard A. (2009)
This study evaluated the effects of tobacco Purchase, Use and Possession (PUP) laws on student perceptions of adolescent tobacco use within towns and schools. Twenty-four towns were randomly assigned into two conditions, the experimental condition (E PUP) involved efforts to increase both PUP law enforcement and reduce minors’ access to commercial sources of tobacco, whereas the control condition (C) focused only on efforts to reduce minors’ access to commercial sources of tobacco. A Hierarchical Linear Modeling analytical approach was selected due to the multilevel data and nested design. The present study found that over time, youth in the experimental PUP condition observed less youth tobacco usage at school and in their town, and perceived lower rates of tobacco among their peers at school and among friends than youth in the control condition. The findings suggest that PUP law enforcement might be used to strengthen community norms against youth tobacco use.